Battle of Spokane Plains petition,
Petition by students from Lewis & Clark High School submitted to W. D. Vincent, Spokane Historian, to apply to the U. S. Geographical Board for an official name for a particular "high rocky point situated in the South East quarter of Section Four, Township twenty five North Range forty two East, Willamette Meridian" The students submitted three maps and two pages of written arguments copied from other historical documents.